Evidence for Stagnation of the Harvard Sublobe (Lake Michigan Lobe) in Northeastern Illinois, U.S.A., from 24 000 to 17 600 BP and Subsequent Tundra-Like Ice-Marginal Paleoenvironments from 17 600 to 15 700 BP - Curry, Brandon; Yansa, Catherine (Géographie physique et Quaternaire, 2004)
AbstractGlacial deposits of the last glaciation associated with the Harvard sublobe (Lake Michigan lobe) in northeastern Illinois, U.S.A., occur between sediment with dateable organics. The lower organics include fragments of Picea sp. as young as 24 000 ± 270 BP. The supraglacial organics occur sparsely in laminated silt and fine sand in landforms that are positioned relatively high on the landscape, such as deposits from ice-walled lakes. These terrestrial organics yield ages that are 2500 to 1300 14C years older than organics at the base of sediment successions in nearby kettle basins. Basal 14C ages from four upland sites range from 17 610 ± 270 to 16 120 ± 80 BP. Our revised time-distance diagram of the Harvard sublobe now reflects a period of stagnation from 24 000 to about 17 600 BP. The supraglacial lacustrine silt yielded plant macrofossil assemblages of primarily tundra plants, including Salix herbacea and Dryas integrifolia. These plants likely grew in supraglacial and ice-marginal environments. The ostracode fauna include Cytherissa lacustris and Limnocythere friabilis. Geomorphic relations and ostracode ecology indicate that more than 17 m of ice buttressed some of the supraglacial lakes.